Management innovation, green product innovation, green process innovation influence on financial performance. A study of South African manufacturing firms. - Takyi Kwabena Nsiah; Ruth A. Danso; Ofori Charles; Mmieh K Raphael (Garuda Prestasi Nusantara Consulting, 2022)
This research aims to evaluate the nexus of green innovation on registered companies' financial performance on the Johannesburg Stock Exchange (J.S.E.). The paper followed the content analysis approach in evaluating green products, green processes, management innovation ability, and green image variables on 64 manufacturing firms from 2011 up to 2018. This article adopted Smart PLS-SEM 3 analyses to check the models suggested for the study empirically. The findings reveal that management innovation ability had a significant favorable influence on the green process; however, the relation with financial performance was insignificant. Green process innovation had a significant negative association with enterprise financial performance. Again, the effect of green process innovation on green products was enormously significant. Green products did not have a considerable influence on financial performance. Finally, the moderating variable green image was introduced into the model, green product, and green process; both indicated an insignificant positive effect on the enterprise financial performance. The conclusion of this research supports the theoretical assertation that mutually green products and green processes are complementary.